Application of Fuzzy Analytical Hierarchy Process in the selection of social networking sites / Nor Aida Nabilah Anuar ...[et al.] - Anuar, Nor Aida Nabilah; Othman, Suziana Aida; Ibrahim, Nurin Fareeha; Zakaria, Nur Azyyati; Wan Nordin, Wan Nurul Husna; Ramli, Masnira (Universiti Teknologi MARA, Kelantan, 2023)
Social networking sites (SNS) have become a ubiquitous part of modern life, with millions of people using SNS to stay in touch, to network, and to share information. SNS also provides a platform for university management to communicate with students and keep them informed about events, deadlines, and other important information. Besides, SNS allows students to access information, resources, and knowledge from a variety of sources, including university staff, other students, and subject-matter experts. With so many options of SNS available, the university management must identify which platform is commonly used by students. Hence, this study proposes a Fuzzy Analytic Hierarchy Process (F AHP) approach to evaluate and rank five popular SNSs: Instagram, Facebook, TikTok, Twitter, and YouTube among students in Universiti Teknologi MARA Cawangan Kelantan (UiTMCK). Five experts were invited to provide a rating of the performance values of criteria, sub-criteria, and alternatives using a linguistic scale. The evaluation is based on four criteria: Content (C1), Functionality (C2), Usability (C3), and Privacy (C4), with another eight sub-criteria. The results demonstrate the effectiveness of the FAHP in selecting the best SNS and indicate that Facebook (A1) is at the first ranking followed by Instagram (A2), TikTok (A3), Twitter (A4), and YouTube (As). Content is identified as the most important criterion with advertisement as the preferred sub-criterion. The findings of the study highlight the importance of utilizing social media platforms to enhance creativity in promoting programs and events, which can increase student participation and engagement in university activities.